Learning Challenges in Secondary Private High Schools in Bangladesh: From Business Studies Students’ Perspective - Md. Kabir Hossain (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
Secondary business education is an essential stream in the general education system of Bangladesh. Quality education is often hampered by the learning challenges faced by learners worldwide, especially in the area of business studies at the secondary level. Business learners are comparatively deprived of different learning opportunities and facilities. Although Education Policy 2010 and the National Curriculum 2012 emphasize on quality of learning for secondary business education students. The purpose of this study is to explore the fundamental learning challenges faced by secondary business studies students in private high schools in Bangladesh, including differences between urban and rural students. The study examines the difficulties students encounter while studying business studies in the secondary private high schools. This research applies both quantitative and qualitative methods, where five rural and five urban private high schools of Chattogram district were selected purposively, and ten students in grades 9 and 10 were chosen from each school randomly for collecting data. Therefore, 100 participants were the sample of this investigation. A survey questionnaire and semi-structured interviews were utilized as tools in collecting data. The key findings indicate that some challenges faced by business students are curriculum-related issues, teacher competence and teaching method, insufficient access to resources, infrastructural facilities, rural-urban disparities, teaching-learning environment, socio-economic and communication barriers. The results reveal that this study will contribute to teachers, educators, policy makers, educational leaders, and the government to address the challenges so that sustainable quality education can be ensured and suggest to improve the curriculum and teaching-learning activities.